Holocene Environmental Changes Inferred From an Aeolian-Palaeosol-Lacustrine Profile in the Mu Us Desert, Northern China - Liu, Xiaokang; Lu, Ruijie; Ding, Zhiyong; Lyu, Zhiqiang; Li, Yijing; Dong, Zhibao (Frontiers in Earth Science, 2021)
An excavated profile of aeolian-palaeosol-lacustrine sediments (the Wapianliang profile), located at the southeastern part of the Mu Us Desert, Northern China, was studied to reconstruct regional Holocene environmental changes. A chronology was established based on three AMS 14C and two OSL dates, and variations in the lithology and grain size, magnetic susceptibility, soil micromorphology, and chemical elements were used to explore the regional depositional environments during the Holocene. The results showed that since around 14 ka BP, this region had experienced seven alternations of wetting and drying. A shallow lake, which was identified by celadon lacustrine sediments with sporadic freshwater gastropod fossils, occurred in this area from around 13.0 ka BP to 9.9 ka BP. There existed two obvious intervals of soil formation, inferred from the environmental proxies of the palaeosol/sandy palaeosol layers, with relatively fine average grain-size, high magnetic susceptibility value, remarkable pedogenesis features, and strong chemical weathering, in particular, a well-developed palaeosol layer dating from the middle Holocene (8.6 ka BP to 4.2 ka BP). A weakly-developed palaeosol layer (from around 1.2 ka BP) at the upper part of the profile is possibly an indication of the Medieval Warm Period. This implies a forest steppe environment at both of these sedimentary stages. After 0.9 ka BP, a desert environment returned, analogous to before around 13.0 ± 1.4 ka BP, between 9.9 ± 1.1 ka BP to 8.6 ka BP, and between 4.2 ka BP to 1.6 ka BP, indicating the aggravation of aeolian activity and the expansion of mobile sand dunes. The variations in sedimentary environments were mainly triggered by changes in the East Asian Summer Monsoon (EASM).